DNA Replication Licensing Affects Cell Proliferation or Endoreplication in a Cell Type–Specific Manner - del Mar Castellano, María (American Society of Plant Biologists, 2004)
In eukaryotic cells, the function of DNA replication licensing components (Cdc6 and Cdt1, among others) is crucial for cell proliferation and genome stability. However, little is known about their role in whole organisms and whether licensing control interfaces with differentiation and developmental programs. Here, we study Arabidopsis thaliana CDT1, its regulation, and the consequences of overriding licensing control. The availability of AtCDT1 is strictly regulated at two levels: (1) at the transcription level, by E2F and growth-arresting signals, and (2) posttranscriptionally, by CDK phosphorylation, a step that is required for its proteasome-mediated degradation. We also show that CDC6 and CDT1 are key targets for the coordination of cell proliferation, differentiation, and development. Indeed, altered CDT1 or CDC6 levels have cell type–specific effects in developing Arabidopsis plants: in leaf cells competent to divide, cell proliferation is stimulated, whereas in cells programmed to undergo differentiation-associated endoreplication rounds, extra endocycles are triggered. Thus, we propose that DNA replication licensing control is critical for the proper maintenance of proliferative potential, developmental programs, and morphogenetic patterns.